Evaluasi Indeks Kenyamanan Taman Kota (Lapangan Puputan Badung I Gusti Ngurah Made Agung) - ROHMAN HADI; KOMANG ARTHAWA LILA; I GUSTI ALIT GUNADI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2012)
ABSTRACT The Comfort Index Evaluation of a City Park: Case Study of Puputan Badung I Gusti Ngurah Made Agung Square, Denpasar - Bali Puputan Badung Square besides of its historical value, it also has an important role as a balance to the city landscape in the form of green open space. It is therefore necessary to evaluate the comfort index of Puputan Badung Square. The purpose of this study is to see the thermal comfort index at Puputan Badung Square, which serves as a city park of Denpasar. The study also sees how vegetation cover has effect on the comfort index in Puputan Badung Square. Moreover, the thermal comfort aspect from the perception of visitors is also measured. The comfort index of this study is measured by using the Thermal Humidity Index (THI) method. The study site is divided in grids of 24 sample plots. The visitors’ perception data of thermal comfort are tabulated, calculated, and tested by using the percentage (%) method and chi square test. The thermal comfort index in Puputan Badung Square shows that the values in May 2012 can be categorized as comfortable. The thermal comfort index in this case besides being affected by the microclimate, it is also affected by the dominance of trees in the observation plots. Keywords: city park, green open spaces, comfort index,